(3GdJacjQ GdPcjs (3KdGKI CehQ CSGSjI dMd GdeTcdGJ, hGdGHJcGQ, hEfLGR GdCehQs - (3eGQceGf, BQJs; (3ChR, eMeOs; (3hjfjJ, cQjL Hjs; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2016)
(3GdcJGH jcTa cjajI Yed GdPGcQI, hcjajI GdJYde HaGYdjI, hcjajI GSJNOGe GdeYQaI YfOeG JMJGL Edj EfLGR GdCehQs
(3GdeMJhjGJ (B: (3eGgh GdJacjQ GdPcj (B-- (3JQSjN GdYGOGJ hGdPcjI hJZjjQ GdSdhcjGJ (B-- (3JYRjR LhOI GdJYde ef NdGd eYQaI MOhOc (B-- (3age BdjI Yed GdCTjGA (B-- (3ELQGA ebGQfGJ hJWHjb eYQaJc (B-- (3RjGOI aGYdjI PGcQJc ddMO GdCbUj (B-- (3GdJacjQ GdPcj HGdeeGQSI GdYedjI (B-- (3Ndb KbGaI GdPcGAs
(3CYdj UaMI GdZdGa (B: (3KdGKI CehQ CSGSjI dMd GdeTcdGJ, hGdEHJcGQ, hEfLGR GdCehQs
(3GdfU eJQLe Edi GddZI GdYQHjI Yf GddZI GdEfLdjRjIs
1 4 12 13
Keywords: (3GdJKbja GdTNUjs; (3GdJYdes; (3GdJacjQs; (3GdJcja GdTNUjs; (3GdJcja GdfaSjs; (3GdYGOIs; (3GdfLGM GdTNUj (Bqrmaks; (3GdfLGMs; (3JbhjI GdPGcQIs